MY FIRST PREPRINT ONLINE: DEVELOPING AN ONLINE MODULE IN RESEARCH WRITING - Evgeniy V. Bakin; Natalia V. Smirnova (Moscow Polytechnic University, 2016)
The paper addresses the experience of developing and implementing an online module in academic writing for university staff. The authors describe the module structure and teaching/learning process from the point of view of the course developers and trainers. The paper overviews the key requirements for developing and running online training in research writing. These requirements might be relevant for those involved in teaching, developing and implementing online support modules in academic writing.